Electromyographical comparison of a traditional and kipping pull-up - Snarr, R. L.; Casey, J. C.; Hallmark, A. V.; Esco, M. R. (Journal of Australian Strength and Conditioning, 2018)
The purpose of this investigation was to compare the electromyographical (EMG) activity of the latissimus dorsi (LD), posterior deltoid (PD), middle trapezius (MT), and biceps brachii (BB) while performing two pull-up variations. Resistance-trained men and women (n = 13, age = 24.26 ± 6.24) volunteered to participate in this study. All participants performed a traditional pull-up (PU) along with a popular variation (i.e., kipping pull-up (KP)). Each pull-up was performed for three repetitions. Normalized (%MVC) EMG values were recorded for each muscle group during each of the variations. The KP provided significantly lower muscular activation values within all muscles examined compared to the PU. The average decreases in muscular activation for the KP when compared to the PU were 10.6% for the LD, 11.5% for the PD, 22% for the PD, and 13.4% for the BB. The KP employs the assistance of the lower body, with an emphasis on the hip joint, to create a power "swing" to aid in propelling the body upwards towards the bar to complete the movement. By employing lower body momentum, the upper body had less of a musculature demand in order to pull the body upwards towards the bar, thereby resulting in significantly lower EMG values compared to the PU. Practitioners should take note that both the and PU and KP variation may provide sufficient values in select muscular groups necessary to achieve improvements in muscular strength and endurance of the shoulder joint and girdle complex. However, if a greater pull-up challenge is warranted then individuals should choose the traditional PU which may provide a greater muscular demand.